15 Ranking and rating severity: stakeholder perspectives of neurodevelopmental impairment after preterm birth. (21st October 2022) - Richter, Lindsay; Chera, Amarpreet; Luu, Thuy-Mai; Bone, Jeffrey N; Bourque, Claude-Julie; Janvier, Annie; Zhang-Jiang, Sofía; Synnes, Anne
Abstract: Background: Children born very preterm are at increased risk of neurodevelopmental impairment (NDI). NDI rates are used to make critical healthcare decisions. The Canadian Neonatal Follow-Up Network (CNFUN) defines severe NDI at age 18–24 months as Bayley-III Cognitive, Motor or Language composite scores <70, need for hearing aids or cochlear implants, bilateral visual impairment or non-ambulatory cerebral palsy (Gross Motor Classification System level 3 or higher). This definition was developed using the perspectives of clinicians and scientists. Stakeholders including parents/caregivers, persons born preterm and community partners have never been asked how they categorize disabilities and rank different impairments. Objectives: To evaluate stakeholder perspective of severity of disability and ranking of different health conditions all defined as severe by CNFUN using clinical vignettes. Design/Methods: Ten clinical vignettes describing 18 month old children with combinations of single and multiple impairments based on the CNFUN definition of severe NDI and one clinical vignette describing a child without NDI (control) were co-developed by clinicians and parents. The survey of 11 vignettes was distributed to: (1) British Columbian parents of very preterm children during follow-up clinic visits; and (2) Canadian and international parents, families, individuals with lived experience with prematurity and/or NDI and their social networks using a snowball sampling technique. Participants rated the severity of each vignette on a scale from 0 (worst possible health) to 10 (best possible health) and answered if they perceived the vignette to represent a severe disability. Results were analyzed descriptively and mean differences from the control were compared using a linear mixed effects model. Results: 827 participants and 4553 vignettes were completed with no significant difference by population sampled. Participants classified the clinical vignettes as describing a severe condition ranging from 5% for the cognitive delay vignette to 55% for the cerebral palsy and language delay vignette. Mean difference in rank compared to control is shown in Figure 1. Only the ranking of the latter vignette was significantly different from the control. Conclusion: Most key stakeholders do not perceive clinical vignettes describing CNFUN definitions of severe NDI as truly severe. Components of severe NDI rank differently but only the cerebral palsy and language delay vignette varies significantly. Current CNFUN definitions of severe NDI need to be revised.